THE ROLE OF GENDER OF UMKM OWNERS IN THE RELATIONSHIP BETWEEN ENVIRONMENTAL SUSTAINABILITY, OPEN INNOVATION, AND UMKM INNOVATION PERFORMANCE - Nuraini, Dewi; Herawati, Wiwik; Prasetya, Hendra (AGUSPATI Research Institute, 2024)
Micro, Small and Medium Enterprise Background (UMKM) plays an important role inining environmental sustainability through sustainable business innovation. Gender, as a component that affects organizational dynamics, can also contribute to the changes made by UMKM to support environmentally friendly business practices. However, there is not much research specifically investigating how gender plays a role in driving UMKM innovation to maintain environmental sustainability. This study uses relevant literature to understand how gender factors influence innovative practices and environmental sustainability in UMKM business. By analysing the literature in depth, this study aims to find patterns of the relationship between gender, business innovation, and sustainability of the environment in the context of UMKM. Therefore, this article is expected to provide a more in-depth insight into how UMKM This research uses the type of meta-analysis research, in which research findings from various researchers are combined. Research results can be accessed by some researchers using Google Scholar or Google Scientist searches to find out how much impact the application of research models, methods, or strategies has. With a sample of literature 10 years before 2024.